Modelling the complexity of emergency department operations using hybrid simulation. (2015) - Ahmad, Norazura; Ghani, Noraida Abdul; Kamil, Anton Abdulbasah; Tahar, Razman Mat
As a system, the emergency department reveals detailed and dynamic complexity of its interaction between inter-departmental units and intra-departmental elements. Discrete-event simulation (DES) has been recognised for its ability to comprehend operational problems with detailed complexity. Whilst using DES to model the complexities of the integrated emergency department system, we also use system dynamics (SD) to capture the interdependency relationships between the emergency department and other subunits in a hospital. This paper presents the integration of DES and SD modelling approach, hereby named as hybrid simulation, to better understand emergency department operations from a whole system perspective.